Poiploidy induction of Indonesian Black Rice Oryza sativa L. Var. Cempo Ireng with Bio-catharantine - Kurniawan, Ludfi; Laili, Alvina Nur; Angraeni, Devi Silvia; ‘Ain, Salsabila Qurrotu; Wulandari, Dyah Retno; Ulum, Fuad Bahrul (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2023)
High demand on black rice Oryza sativa L. due to their high antioxydant content and better nutrition than the white rice. On the other hand this high price rice still less interest for the farmet to cultivate it. Therefore, improvement of plant characters was carried out through polyploid induction using the natural anti-mitotic compound bio-catharanthine. The purpose of this study was to test the effectiveness of bio-catharanthine in inducing polyploidy in Cemp ireng black rice. This study used a two-factor completely randomized design (CRD) method with three replications. The treatment factor of bio-catharanthine concentration was 1%, 1.5 %, 2 %, 2 %, 2.5 % and 3 % with the soaking time of 48 hours. The germination rate, ploidy level, stomatal size and density, and antioxidant were measuret to observed the characteristic of the mutan. The results showed that the treatments of 3 % bio-catharanthine enhanced the chromosome number of black rice Cempo ireng. Biocatharantine did not affected the germination rate through the treatments. Out mutants shows alternation on the stomatal size and density. The antioxidant of leaf sample did not changed after the treatment. Bio-catharanthine on high concentration migh be possible to be applied on polyploidy induction in black rice